2021
DOI: 10.1371/journal.pone.0254066
|View full text |Cite
|
Sign up to set email alerts
|

Male gender is a predictor of higher mortality in hospitalized adults with COVID-19

Abstract: Introduction The coronavirus disease 2019 (COVID-19) pandemic continues to be a global threat, with tremendous resources invested into identifying risk factors for severe COVID-19 illness. The objective of this study was to analyze the characteristics and outcomes of male compared to female adults with COVID-19 who required hospitalization within US academic centers. Methods Using the Vizient clinical database, discharge records of adults with a diagnosis of COVID-19 between March 1, 2020 and November 30, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
108
10
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(155 citation statements)
references
References 5 publications
31
108
10
6
Order By: Relevance
“…To this regard, it has been already reported that rates of anemia in men increased monotonically with age, while that of women increased bimodally with peaks in age groups 40–49 years and 80–85 years [ 19 ]. Furthermore, older COVID-19 patients have a higher risk of mortality, but in this case, women with anemia seem to have a worse outcome compared to males who generally have been reported to be at higher risk of death [ 20 ]. This difference can be explained by considering that some research has shown that the risk for CKD is slightly greater in women than in men [ 21 ] and that prominent gender disparities in CKD prevalence do exist among different countries [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…To this regard, it has been already reported that rates of anemia in men increased monotonically with age, while that of women increased bimodally with peaks in age groups 40–49 years and 80–85 years [ 19 ]. Furthermore, older COVID-19 patients have a higher risk of mortality, but in this case, women with anemia seem to have a worse outcome compared to males who generally have been reported to be at higher risk of death [ 20 ]. This difference can be explained by considering that some research has shown that the risk for CKD is slightly greater in women than in men [ 21 ] and that prominent gender disparities in CKD prevalence do exist among different countries [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…To further appraise the impact of potential baseline confounders, a meta-regression analysis using age, gender, HT, DM, chronic pulmonary disease and hyperlipidaemia as moderator variables was performed. These variables were selected since previous analyses have identified those comorbidities as independent predictors of mortality in COVID-19 patients [2,3,10,11]. All meta-analyses were conducted using Comprehensive Meta-Analysis software, version 3 (Biostat, Englewood, NJ, USA).…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…Multiple studies have addressed clinical outcomes in COVID-19 patients: many of them have shown a correlation of mortality with advanced age and male gender; some have shown an association with smoking and certain chronic comorbidities, such as underlying diabetes mellitus, chronic renal insufficiency, chronic obstructive lung disease, and cardiovascular diseases; some have addressed clinical parameters, such as the severity of respiratory failure [ 8 ] and acute renal failure; and others have addressed laboratory investigations as predictors of outcome and found significant correlations with certain inflammatory markers, such as high-sensitivity C-reactive protein, D dimer, and procalcitonin [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%